2006
DOI: 10.1056/nejmoa055119
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ondansetron for Gastroenteritis in a Pediatric Emergency Department

Abstract: In children with gastroenteritis and dehydration, a single dose of oral ondansetron reduces vomiting and facilitates oral rehydration and may thus be well suited for use in the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
248
4
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(267 citation statements)
references
References 20 publications
10
248
4
5
Order By: Relevance
“…41 Ondansetron usage remained limited to patients who suffered from nausea following chemotherapy until a decade ago when research began to emerge supporting its use in children with acute gastroenteritis. 19,42 Although it is primarily used for children visiting the ED for gastroenteritis, 43 it is not constrained to that group of children. A retrospective study of ondansetron in the ED reported that 38% (n = 12,620) of prescriptions were for reasons other than gastroenteritis in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Ondansetron usage remained limited to patients who suffered from nausea following chemotherapy until a decade ago when research began to emerge supporting its use in children with acute gastroenteritis. 19,42 Although it is primarily used for children visiting the ED for gastroenteritis, 43 it is not constrained to that group of children. A retrospective study of ondansetron in the ED reported that 38% (n = 12,620) of prescriptions were for reasons other than gastroenteritis in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…19 There was no previous study to determine the optimal duration of treatment. Previous studies have failed to show an impact of multiple doses in comparison to a single dose for other disease.…”
Section: Interventionmentioning
confidence: 99%
“…26 Several studies report ondansetron use in vomiting of gastroenteritis in children. Three studies examined the use of oral ondansetron 21,22,27 and one study examined the use of IV ondansetron 20 for vomiting due to acute gastroenteritis were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have also evaluated the use of ondansetron in children with vomiting from gastroenteritis. 4,[20][21][22] Drug utilization studies of anti-emetic drugs were carried out in Sri Lanka, Italy and multi country trial 6,14,23 similar studies particularly in children is lacking in India so we decided to conduct this study in our hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of pediatric studies have documented the drug's efficacy in treating vomiting secondary to acute gastroenteritis, where it increases the success of oral rehydration therapy and reduces the need for hospitalizations (1,2). Ondansetron has become the preferred antiemetic in children and adults because of its superior efficacy and low rate of adverse events.…”
Section: Introductionmentioning
confidence: 99%